Controlling w obszarze zarządzania usługami długoterminowymi - Kasperowicz, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Problem of long - term services it is complex and deferent subject. Companies which realize long - term services can use that for management of long - term services in long and short periods in the frame of dedicate controlling. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 111-117